Biomimetic Nanoparticles as a Theranostic Tool for Traumatic Brain Injury. (26th March 2021) - Zinger, Assaf; Soriano, Sirena; Baudo, Gherardo; De Rosa, Enrica; Taraballi, Francesca; Villapol, Sonia
Abstract: Traumatic brain injury (TBI) triggers both central and peripheral inflammatory responses. Existing pharmacological drugs are unable to effectively and quickly target the brain inflamed regions, setting up a major roadblock towards effective brain trauma treatments. Nanoparticles (NPs) have been used in multiple diseases as drug delivery tools with remarkable success due to their rapid diffusion and specificity in the target organ. Here, leukocyte‐based biomimetic NPs are fabricated as a theranostic tool to directly access inflamed regions in a TBI mouse model. This NP systemic delivery is visualized using advanced in vivo imaging techniques, including intravital microscopy and in vivo imaging system. The results demonstrate selective targeting of NPs to the injured brain and increased NPs accumulation among the peripheral organs 24 h after TBI. Interestingly, increased microglial proliferation, decreased macrophage infiltration, and reduced brain lesion following the NPs treatments compared to sham vehicle‐treated mice are also found. In summary, the results suggest that NPs represent a promising future theranostic tool for TBI treatment. Abstract : Leukosomes are fabricated using lipids mixed with membrane proteins extracted from cultivated leukocytes. Leukosomes are tested in vivo using a traumatic brain injury (TBI) mouse model and demonstrated increased targeting to inflamed organs following TBI in both sexes.